EOSC and the Free Riders - Gfrerer, Margareth; Mogus, Solomon (My University, 2016)
Big Data, Open Science and Technology are the topics on the agenda of the European Commission (EC) on one side and on the other side, ministries, research funding organizations, universities and public research institutions together with university libraries are bringing complaints about the access to scientific publications and research data also to the EC. Against these facts the EC has taken on the responsibility to realize the idea of Open Science and to favour the implementation of an European Open Science Cloud (EOSC), which “aims to develop a trusted, open environment for the scientific community for storing, sharing and reusing scientific data and results” (COM 2016). A High Level Expert Group (2016) has worked on the definition, the key trends in Open Science and the answer, how EOSC will be realized for the target group of European researchers and professionals in science and technology. The EOSC is an EU Member State Project. Non-European researchers can join the EOSC as free riders. Based on the findings of the HLEG this research will explore the question: What is the advantage for a research community from an emerging country to get a free rider position on the EOSC? This research is primarily a literature review. Discussions with international researchers and Ethiopian university management presents insights about the advantages of a free ride position on the EOSC. An overview between the free rider problem as discussed in economic literature and the invitation to free ride on WIKIPEDIA and EOSC will conclude this research.
Keywords: Open Access; Open Science; 4th industrial revolution; free riding; innovation; Big Data